WRITING PROCEDURE TEXT BY USING SMALL GROUP WORK STRATEGY - Yeni Erlita (BAHAS, 2017)
Writing procedure text is considered as one of genre in writing. It is enjoyable to write procedure text writing.Small group work strategy is considered as a solution for students' problem in generating and organizing ideas. Therefore, the writer is convinced that by using Small group work strategy teaching learning process will be more successful, especially in teaching and learning procedure text.In this study, the product in writing content, organization, vocabulary, language use, and mechanics.The data was calculated by using the score of writing test. The analysis was intended to get the significant differences between taught by using small group work strategy and taught by individual work in writing procedure text.The result of this study shows that there is difference of out between both of groups. Based on statistics calculation, the mean of control group and experimental group is different. The mean score of the experimental group is higher than control group. The calculation of the t-test shows that t-observed (3,37) is higher than t-table value (2,000) for the degree of freedom  58 at the lord significance (a) 0,05. The result in writing taught by using small group work strategy was higher than taught by using individual work strategy in writing procedure text. Keywords: Writing, Procedure text, Small group work strategy, Individual work.